Nobel Lecture: The Transformation of Macroeconomic Policy and Research - Prescott, Edward C. (Journal of Political Economy, 2006)
What I am going to describe for you is a revolution in macroeconomics, a transformation in methodology that has reshaped how we conduct our science. Prior to the transformation, macroeconomics was largely separate from the rest of economics. Indeed, some considered the study